Is the MTHFR C677T polymorphism associated with obesity risk? – a meta-analysis. - Costa, J. (2016)
Overweight and obesity are a major worldwide health problem and its incidence is increasing every year. Methylenetetrahydrofolate reductase (MTHFR) plays an important role in folate metabolism and as a regulator of DNA methylation, synthesis, and repair. MTHFR gene is polymorphic at nucleotides 677 (C→T) and 1298 (A→C). MTHFR C677T polymorphism results in alloenzymes with decreased activity and several studies have pointed to association between the MTHFR C677T polymorphism and overweight/obesity risk.